Modelo pronóstico para la producción de caña de azúcar en la Empresa Agroindustrial Laredo S.A.A periodo enero 2012 – noviembre 2019 - Valverde Nolasco, Lehder David (2021)
This research is descriptive, the main objective being to determine the model that best _x000D_ predicts the monthly production of sugarcane in the Empress Agro-industrial Laredo _x000D_ S.A.A. in the period January 2012 - November 2019, a non-probability sampling was _x000D_ performed. A sample of 95 records was obtained from the monthly reports of sugarcane _x000D_ production (metric tons) in the period from January 2012 to November 2019. The _x000D_ variable of study was Production of sugar cane (tons / month), a time series model was _x000D_ performed using the Box-Jenkins methodology finding that the most appropriate model _x000D_ was an ARIMA (1, 1, 12), the AR coefficients (- 0.229527) and MA (0.726968) which _x000D_ were highly significant with P values of 0.001 and 0.000 respectively. It is concluded that _x000D_ the model for the Production of sugar cane of the Agro-industrial Company Laredo _x000D_ S.S.A. Period January 2012 - November 2019